TINJAUAN PERLINDUNGAN HUKUM TERHADAP PELAKU LAYANAN KESEHATAN SECARA ONLINE - Putong, Diana Darmayanti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Health is a crucial factor in human life. It is an important element in achieving the common welfare and is enshrined in the Preamble of the Constitution of the Republic of Indonesia of 1945 concerning the general welfare. Therefore, health is considered a basic need and a right for every individual. In recent decades, the disciplines of medicine and law have become increasingly intertwined. Online health services have become one of the breakthroughs today that are expected to provide effective and efficient health services. This online health service is commonly known as an online clinic. Online clinic services have both positive and negative impacts. On one hand, online clinic services facilitate the process of health services between doctors and patients without being limited by distance. However, online clinics can threaten patient confidentiality. There are also issues in medical practice in online services because the diagnosis process is carried out online without face-to-face contact with the patient, which could lead to misdiagnosis of patients. This article focuses on the legal protection for online clinic practitioners. The result of this article is that the legal status of online clinics in Indonesia is still unclear because there is no specific regulation that governs online clinics in legislation. Therefore, there is a legal vacuum in the practice of online clinics.